Away-from-home food consumption of students from some courses in the health area of a private university - Moreno Duarte, Flávia; Darlen Soares de Almeida, Suzy; Anusca Martins, Karine (O Mundo da Saúde, 2013)
This study aimed to characterize the food eaten away from home by students from the health area at a private university in Goiania, Goiás. This was a cross-sectional and descriptive study with 101 nursing, nutrition and physiotherapy students in an undergraduate institution in the State of Goiás. Socio-demographic data and data about away-from-home food consumption habits were collected and a descriptive analysis was carried out. Most subjects were female (85.1%) and were aged between 18 and 21 (68.3%). From these, 84.2% stated that they tended to eat outside their home, 70.3% had already gotten sick after eating street food and 63.4% reported that their physical appearance influenced their food choices. The meals with a higher frequency of consumption outside home were: lunch (32.7%), afternoon snacks (24.8%) and light meals (20.8%) and the most consumed foods were: dairy products (43.2%), fruits (35.8%), sweets (26.3%), savory snacks (25.3%) and cookies (20.0%). Nutrition students look for healthy food to eat when away from home, while nursing and physical therapy students had a high intake of recognized unhealthy food. Lunch is the meal with a higher frequency of consumption outside home and “by-the-kilo” restaurants were the most frequented type.